Exploring molecular genetics of bladder cancer: lessons learned from mouse models - Imran Ahmad; Owen J. Sansom; Hing Y. Leung (The Company of Biologists, 2012)
Urothelial cell carcinoma (UCC) of the bladder is one of the most common malignancies worldwide, causing considerable morbidity and mortality. It is unusual among the epithelial carcinomas because tumorigenesis can occur by two distinct pathways: low-grade, recurring papillary tumours usually contain oncogenic mutations in FGFR3 or HRAS, whereas high-grade, muscle-invasive tumours with metastatic potential generally have defects in the pathways controlled by the tumour suppressors p53 and retinoblastoma (RB). Over the past 20 years, a plethora of genetically engineered mouse (GEM) models of UCC have been developed, containing deletions or mutations of key tumour suppressor genes or oncogenes. In this review, we provide an up-to-date summary of these GEM models, analyse their flaws and weaknesses, discuss how they have advanced our understanding of UCC at the molecular level, and comment on their translational potential. We also highlight recent studies supporting a role for dysregulated Wnt signalling in UCC and the development of mouse models that recapitulate this dysregulation.